Design of a force control gripper using Matlab Simulink - Shishkovski, Dejan; Pecioski, Damjan; Anachkova, Maja; Mickoski, Hristijan; Pandilov, Zoran (IEEE, 2023)
The working body usually called the gripper in manipulators is an essential component of industrial automation systems. They are designed to hold and manipulate objects with precision, speed, and reliability. Robotic applications and the creation of functional organs are both widespread. The working body may be incorporated into the robot's overall design or added to its fundamental framework. The design is determined by the robot's function, the object it must grasp, the task it must complete, and its working environment. Force control is an essential feature of robotic grippers that allows them to handle delicate or fragile objects without causing damage. This paper outlines the many decisions that are made when designing and selecting the robot's gripper. Aspects of the process and environment are covered first. Power, joint adaptability, load capacity, and connections are all included. Following is a section that offers an overview of the various working bodies and their constructive directions. The sensors and elements of the control system are also featured.
Keywords: robot gripper, force control, CAD model, Simulink model